Biochar adsorbent as well as preparation method and application thereof
By heating and degrading and ball milling of ginkgo leaves, and adding transition metal salt solution to modify, high-efficiency biochar adsorbent was prepared, which solved the problem of insufficient adsorption capacity of existing biochar to SO42- and achieved SO42- in mine water Efficient processing and harmless utilization of resources.
Patent Information
- Application Number
- CN202411454885.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-27
AI Technical Summary
The existing biochar has poor adsorption capacity of SO42 in wastewater and cannot meet the needs of specific pollutants in mine water.
By heating and degrading the ginkgo leaves and ball milling, adding transition metal salt solution for modification, an efficient biochar adsorbent was prepared, and the modified surface functional groups were used to improve the adsorption capacity of SO42-.
It realizes efficient adsorption of SO42- in mine water, reduces the cost of sewage treatment, and the process is green and environmentally friendly. The raw materials are waste resource-based, and secondary pollution is avoided.
Smart Images

Figure CN119186495A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of environmental protection technology, and in particular to a biochar adsorbent, a preparation method thereof and an application thereof. Background Art
[0002] Coal resources are the foundation of my country's industrial development, but in the process of coal mining, a large amount of mine water needs to be discharged. According to statistics, about 2 tons of mine water are produced for every ton of coal mined in my country. Although most of the pollutants in the discharged mine water can meet the Class III emission limits of "GB3838-2002 Surface Water Environmental Quality Standard", some of the sulfate ions (SO4 2- ) but cannot meet the emission standards (<250mg / L).
[0003] SO4 2- It is considered non-toxic, but in practice, high concentrations of SO4 2- It will cause the pH value of the water to decrease, thus causing the death of aquatic plants and animals. Anaerobic sulfate microorganisms in the natural environment will also convert SO4 2- It is reduced to H2S, which is a toxic gas with a foul odor that seriously pollutes the atmosphere and corrodes pipes. In addition, SO4 2- Usually it combines with some metal cations to form sulfate. When high-concentration sulfate wastewater seeps into farmland, it will destroy the soil structure and cause soil salinization, which will eventually lead to a decrease in the yield of agricultural products and uneven product quality. 2- Drinking water that is not suitable for drinking can cause symptoms such as loss of taste, diarrhea, and indigestion.
[0004] Therefore, my country's "Supplementary Project for Centralized Drinking Water Surface Water Sources" (GB3838-2002) and "Drinking Water Hygiene Standard" (GB5749-2006) strictly stipulate the SO4 2- The content of SO4 in wild rice field irrigation water should not exceed 250 mg / L, and some countries have more stringent regulations. For example, the Minnesota Pollution Control Agency in the United States stipulates that SO4 2- The content shall not exceed 10mg / L.
[0005] Adsorption is considered to be the most promising SO4 treatment method due to its advantages of low treatment cost, simple operation, high efficiency and environmental protection. 2-One of the deep removal methods. At present, common adsorption materials include activated carbon, cellulose, hydrotalcite, resin materials and biochar. Among them, biochar is a highly aromatic and functional group-rich porous material produced by heating biomass (crop straw, livestock and poultry manure, sugarcane bagasse, etc.) at 300-800°C under anoxic conditions. Due to its wide range of raw materials, simple preparation, excellent adsorption performance and strong resistance to decomposition, biochar is widely used to remove pollutants from water bodies.
[0006] However, ordinary biochar is not selective for wastewater with complex pollutants and cannot meet the needs of treating specific pollutants in actual wastewater treatment. Therefore, how to provide a biochar suitable for treating SO4 in mine water? 2- Biochar is of great significance to the harmless treatment and resource utilization of mine water. Summary of the invention
[0007] The main purpose of the present invention is to provide a biochar adsorbent, a preparation method and application thereof, so as to solve the problem of biochar adsorbing SO4 in wastewater in the prior art. 2- Poor adsorption capacity.
[0008] In order to achieve the above-mentioned purpose, according to the first aspect of the present invention, a method for preparing a biochar adsorbent is provided, the preparation method comprising: sequentially heating and degrading ginkgo leaves and subjecting them to ball milling treatment to obtain a crude biochar; and adding a transition metal salt solution to the crude biochar for modification treatment to obtain a biochar adsorbent.
[0009] Furthermore, the ginkgo leaves are acid-treated ginkgo leaves; preferably, the temperature for heating degradation is 500-700° C.; preferably, the time for heating degradation is 4-6 hours.
[0010] Furthermore, the grinding speed of the ball milling treatment is 300-350 rpm; preferably, the time of the ball milling treatment is 2-3 h.
[0011] Furthermore, the transition metal salt solution includes: ZrOCl2·8H2O and FeCl3; preferably, the modification treatment includes: adding the crude biochar and the transition metal salt solution into deionized water, and performing a first stirring in sequence to obtain a modified treatment liquid; adjusting the pH value of the modified treatment liquid, performing a second stirring and standing, thereby completing the modification treatment of the crude biochar.
[0012] Furthermore, in terms of mass ratio, the mass ratio of ZrOCl2·8H2O to FeCl3 is 7:3; preferably, the pH value of the modified treatment liquid after adjustment is 10-11.
[0013] Furthermore, after the modification treatment, the preparation method further comprises: washing, centrifuging and drying the modified biochar with water and ethanol in sequence.
[0014] In order to achieve the above object, according to a second aspect of the present invention, a biochar adsorbent obtained by the above preparation method is provided.
[0015] In order to achieve the above object, according to the third aspect of the present invention, there is provided a biochar adsorbent obtained by the above preparation method for adsorbing SO4 in mine water. 2- Application in.
[0016] In order to achieve the above-mentioned purpose, according to the fourth aspect of the present invention, a method for regenerating the biochar adsorbent obtained by the above-mentioned preparation method is provided, and the regeneration method comprises: washing the adsorption saturated biochar adsorbent with deionized water, bathing it in a NaOH solution and drying it to obtain a regenerated biochar adsorbent.
[0017] Furthermore, the water bath treatment includes: immersing and stirring the adsorption saturated biochar adsorbent in a NaOH solution, and then washing it to neutrality; preferably, the concentration of the NaOH solution is 0.1-0.15 mol / L; preferably, the temperature of the water bath treatment is 25-26°C; preferably, the immersion time is 12-14h; preferably, the regeneration number of the biochar adsorbent is ≤4 times.
[0018] The technical scheme of the present invention is applied to prepare a modified biochar adsorbent by pyrolysis, ball milling and transition metal loading of ginkgo leaves. The advantages of the present invention are that the raw material ginkgo leaves used are waste resources, achieving the purpose of treating waste with waste, and the production and preparation process is green, environmentally friendly, simple and easy to operate, and can effectively reduce SO4 in mine water. 2- The adsorption treatment effect is efficient and there is no secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0020] Figure 1 A schematic diagram of the process for preparing a biochar adsorbent according to the present application is shown;
[0021] Figure 2 The figure shows the effect of biochar adsorbent ZrFe-BC on the removal rate of sulfate in the solution under different pH conditions in test experiment 1;
[0022] Figure 3 The figure shows the effect of biochar adsorbent ZrFe-BC on the removal rate of sulfate in the solution under different initial sulfate concentrations in test experiment 2;
[0023] Figure 4 The results show the effects of different concentrations of regeneration agent on the desorption rate of ZrFe-BC and SO4 on biochar adsorbent in test 3. 2- Effect of removal rate on the results;
[0024] Figure 5 The graph shows the effect of the number of regeneration times on the adsorption performance of biochar adsorbent ZrFe-BC in test experiment 3. DETAILED DESCRIPTION
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0026] In a first typical embodiment of the present application, a method for preparing a biochar adsorbent is provided, the method comprising: sequentially heating and degrading ginkgo leaves and subjecting them to ball milling treatment to obtain a crude biochar; and adding a transition metal salt solution to the crude biochar for modification treatment to obtain a biochar adsorbent.
[0027] The ginkgo leaves used in this application mainly contain lignin and cellulose. The ginkgo leaves are degraded by heating to generate biochar, wherein the pyrolysis includes dehydration, decarboxylation, aromatization, etc. The cellulose is pyrolyzed into carbon nanoparticles and carbon microcrystals, and the lignin is pyrolyzed into large particles. After ball milling, the biochar is graphitized to the nanometer level, and the hydroxyl functional groups in the surface pores will react with SO4 2- Ion exchange occurs, and then the transition metal is modified to further improve the SO4 2- For the purpose of adsorption.
[0028] In order to further degrade the lignin and cellulose in the ginkgo leaves as completely as possible, in a preferred embodiment, the ginkgo leaves are acidified ginkgo leaves; preferably, the temperature for heating degradation is 500-700° C.; preferably, the time for heating degradation is 4-6 hours.
[0029] In order to further increase the specific surface area of the biochar, in a preferred embodiment, the grinding speed of the ball milling treatment is 300-350 rpm; preferably, the ball milling treatment time is 2-3 h.
[0030] In order to further improve the biochar's SO4 2- In a preferred embodiment, the transition metal salt solution includes: ZrOCl2·8H2O and FeCl3; preferably, the modification treatment includes: adding the crude biochar and the transition metal salt solution into deionized water, and sequentially performing a first stirring to obtain a modified treatment liquid; adjusting the pH value of the modified treatment liquid, performing a second stirring and standing, thereby completing the modification treatment of the crude biochar.
[0031] The biochar of the present application is loaded with zirconium iron oxide, and when used, it can be placed in a solution to form ZrO(OH)2, which reacts with SO4 2- The following reaction will occur to further improve the SO4 2- Purpose of adsorption:
[0032] ZrO(OH)2+SO4 2- =ZrOSO4+2OH - Formula Ⅰ.
[0033] In order to further improve the efficiency of biochar modification, in a preferred embodiment, the mass ratio of ZrOCl2·8H2O to FeCl3 is 7:3; preferably, the pH value of the modified treatment liquid after adjustment is 10-11.
[0034] In order to further obtain a biochar adsorbent suitable for preservation applications, in a preferred embodiment, after the modification treatment, the preparation method further comprises: washing the modified biochar with water and ethanol in sequence, centrifuging and drying.
[0035] In a second typical embodiment of the present application, a biochar adsorbent obtained by the above-mentioned preparation method is provided.
[0036] In a third typical embodiment of the present application, the biochar adsorbent obtained by the above preparation method is provided to adsorb SO4 in the solution. 2- Application in.
[0037] In a fourth typical embodiment of the present application, a method for regenerating the biochar adsorbent obtained by the above-mentioned preparation method is provided, and the regeneration method comprises: washing the adsorption saturated biochar adsorbent with deionized water, bathing it in a NaOH solution and drying it to obtain a regenerated biochar adsorbent; preferably, the number of times the biochar adsorbent can be regenerated is ≤ 4 times. The biochar adsorbent of the present application can also be regenerated after use to improve the utilization rate of the biochar adsorbent and further reduce the production cost of the biochar adsorbent.
[0038] In order to further regenerate the saturated biochar adsorbent more thoroughly for subsequent use, in a preferred embodiment, the water bath treatment includes: immersing and stirring the adsorption saturated biochar adsorbent in a NaOH solution, and then washing it to neutrality; preferably, the concentration of the NaOH solution is 0.1-0.15 mol / L; preferably, the temperature of the water bath treatment is 25-26°C; preferably, the immersion time is 12-14h; preferably, the biochar adsorbent can be regenerated ≤4 times.
[0039] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0040] The sources of the raw materials used in the examples of the present application are as follows: ginkgo leaves were picked from under ginkgo trees; sodium hydroxide was purchased from Beijing Myrida Technology Co., Ltd.; zirconium oxychloride octahydrate was purchased from Sinopharm Chemical Reagent Co., Ltd.; and ferric chloride was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0041] The experimental simulated wastewater is a solution prepared with a concentration of 1000 mg / L NaSO4 and diluted at different times; NaSO4 was purchased from Shanghai Aladdin, with physical properties of analytical grade, white powder, purity ≥ 97.0%; water: Wahaha purified water.
[0042] Example 1 (preparation process as Figure 1 (shown)
[0043] The ginkgo leaves acidified with hydrochloric acid were heated and degraded at 700°C for 6 hours, and then ball-milled in a high-energy ball mill at a speed of 300 rpm for 2 hours to obtain crude biochar.
[0044] Then, ZrOCl2·8H2O, FeCl3 and 0.5g biochar were added to 100mL deionized water in a mass ratio of 7:3, and the mass ratio of the total mass of ZrOCl2·8H2O and FeCl3 to the biochar was 0.21. The first stirring was performed for 1h, and then NaOH solution was added to adjust the pH to 10. After the second stirring for 1h, it was allowed to stand for 30min. The modified biochar was washed with water and ethanol in turn, centrifuged and dried to obtain the biochar adsorbent ZrFe-BC.
[0045] Example 2
[0046] The ginkgo leaves acidified with hydrochloric acid were heated and degraded at 600°C for 6 hours, and then ball-milled in a high-energy ball mill at a speed of 300 rpm for 2 hours to obtain crude biochar.
[0047] Then, ZrOCl2·8H2O, FeCl3 and 0.5g biochar were added to 100mL deionized water in a mass ratio of 7:3, and the mass ratio of the total mass of ZrOCl2·8H2O and FeCl3 to the biochar was 0.21. The first stirring was performed for 1h, and then NaOH solution was added to adjust the pH to 10. After the second stirring for 1h, it was allowed to stand for 30min. The modified biochar was washed with water and ethanol in turn, centrifuged and dried to obtain the biochar adsorbent ZrFe-BC.
[0048] Example 3
[0049] The ginkgo leaves acidified with hydrochloric acid were heated and degraded at 500°C for 6 hours, and then ball-milled in a high-energy ball mill at a speed of 300 rpm for 2 hours to obtain crude biochar.
[0050] Then, ZrOCl2·8H2O, FeCl3 and 0.5g biochar were added to 100mL deionized water in a mass ratio of 7:3, and the mass ratio of the total mass of ZrOCl2·8H2O and FeCl3 to the biochar was 0.21. The first stirring was performed for 1h, and then NaOH solution was added to adjust the pH to 10. After the second stirring for 1h, it was allowed to stand for 30min. The modified biochar was washed with water and ethanol in turn, centrifuged and dried to obtain the biochar adsorbent ZrFe-BC.
[0051] Test 1: Study on the adsorption effect of biochar adsorbent on sulfate at different pH values in mine water
[0052] Since the change of solution pH value will affect the surface charge of the adsorbent, in order to better study the application of ZrFe-BC material in sulfate solution, it is necessary to further study the adsorption capacity of the adsorbent of this application under different pH conditions. 2- The solution was prepared by adjusting the pH value of the solution to 2, 4, 6, 8, and 10 with 0.1 mol / L HCl or NaOH, and the bottle was sealed with a stopper.
[0053] Under different pH conditions, the ZrFe-BC material obtained in Example 1 was used to treat the above-mentioned SO4 2- The solution was adsorbed, and the conical flask was placed in a constant temperature shaking incubator, shaken at 25°C and 150rpm for 2h, and filtered and sampled every 5min to analyze SO4 2- Two parallel samples were set for each pH value, and the initial sulfate concentration and sampling concentration were tested using the national standard method. The changes in removal rate are shown in the figure below. Figure 2 shown.
[0054] It can be seen that when the solution pH is 2.0, ZrFe-BC has a strong affinity for SO4 2- The adsorption effect was the best. When the adsorption time was 60 min, the pH value of the solution increased from 2.0 to 8.0, and the removal rate gradually decreased from 99.898% to 0.126%. In particular, in the two ranges of pH 2.0-4.0 and pH 6.0-8.0, SO4 2- The removal rate decreased rapidly, from 65.955% at pH 6 to 0.126% at pH 8. In the pH range of 4.0 to 6.0, ZrFe-BC had a significant effect on SO4 2-The adsorption capacity of SO4 decreased slowly, and the removal rate dropped from 86.531% at pH = 4 to 65.955% at pH = 6. 2- The variation of adsorption amount with solution pH may be related to the surface charge of ZrFe-BC.
[0055] When pH < 6.2, the hydroxyl groups (-OH) on the surface of ZrFe-BC are protonated and react with SO4 2- The electrostatic attraction is enhanced; when pH>6.2, the ZrFe-BC surface is deprotonated at high pH, resulting in SO4 2- The electrostatic repulsion to anions increases, and SO4 2- In addition, when the pH value is high, there are a large number of hydroxide ions (OH - ), OH- and SO4 2- The competition for active adsorption sites on the surface of ZrFe-BC will also lead to a decrease in the adsorption capacity of ZrFe-BC, which also explains the SO4 2- The reason why the adsorption amount decreases rapidly.
[0056] Test 2: Study on the adsorption effect of biochar adsorbent on sulfate at different sulfate concentrations in mine water
[0057] Take 100mL of sulfate solution with initial concentrations of 300mg / L, 350mg / L, 400mg / L, 450mg / L, and 500mg / L in a 250mL conical flask, and add 0.5g of the ZrFe-BC material obtained in Example 1, adjust the pH to 3 with 0.1mol / L HCl solution, seal with a sealing film and place in a constant temperature water bath, stir at a constant temperature (25°C) at 200rpm for 2h, filter the water sample after adsorption through a 0.45μm glass fiber filter membrane, and dilute to less than 80mg / L. Detect the initial sulfate concentration and sampling concentration by the national standard method, test the absorbance of the filtrate, and calculate the concentration. Set up 2 groups of parallel experiments, Figure 3 This is a trend chart of sulfate ion removal rate changing with the change of initial concentration.
[0058] It can be seen that when the dosage of ZrFe-BC is 0.5 g, the solution pH is 3, and the adsorption time is 90 min, the removal rate of sulfate ions by ZrFe-BC shows a gradually decreasing trend with the increase of initial concentration.
[0059] The sulfate removal rate dropped from 89.15% at the initial sulfate ion concentration of 300 mg / L to 66.972% at 350 mg / L, then slightly decreased to 65.842% at 400 mg / L, and then dropped sharply to 49.046% at 450 mg / L, and finally to 45.014% at 500 mg / L. Under the condition of a certain adsorbent dosage, the adsorption sites and adsorption capacity are limited, so the removal rate will decrease with the increase of initial concentration. At the same time, the concentration difference of sulfate ions on the solution and the surface of ZrFe-BC is the driving force for solid-liquid mass transfer. When the concentration difference increases, the concentration gradient driving force will also increase, promoting adsorption, thereby increasing the adsorption of sulfate per unit mass of adsorbent, and the adsorption amount shows an upward trend.
[0060] In addition, the ZrFe-BC materials obtained in Examples 2 and 3 were used to adsorb a solution with a sulfate ion concentration of 300 mg / L. After 90 minutes of adsorption, the sulfate removal rate of the ZrFe-BC material obtained in Example 2 was 88.05%, and the sulfate removal rate of the ZrFe-BC material obtained in Example 2 was 87.78%.
[0061] ZrFe-BC to SO4 2- The removal rates of ZrFe-BC all showed an upward trend first and then stabilized with the increase of time, showing the characteristics of "rapid adsorption and slow equilibrium". For ZrFe-BC, in the first 10 minutes of the adsorption reaction, the removal rate increased rapidly, and the adsorption amount also increased rapidly. After 25 minutes, the removal rate gradually tended to be flat, indicating that the adsorption amount also tended to be flat. At about 45 minutes, the adsorption reached saturation.
[0062] Detection experiment 3: Study on the effect of biochar adsorbent on SO4 in mine water 2- Adsorption regeneration capacity
[0063] Adsorption: Take 0.5 g of the ZrFe-BC material obtained in Example 1 into a 250 mL conical flask, add 100 mL of a sulfate solution with an initial concentration of 300 mg / L, adjust the pH to 3, seal the conical flask with a sealing film, place it in a constant temperature water bath, set the water bath temperature to 25°C, the speed to 200 rpm, react for 1 hour, and measure the concentration of sulfate ions in the water sample after the reaction is completed.
[0064] Desorption: Wash the saturated ZrFe-BC with deionized water for 5-6 times, place it in a 250mL conical flask, add 50mL of 0.01, 0.03, 0.05, 0.1, 0.12mol / L NaOH solution, set the water bath temperature to 25℃, the speed to 200rpm, soak for 12h, take it out, wash it with deionized water until it is neutral, and dry it in an oven at 105℃ for later use; at the same time, determine and calculate the SO4 in the eluent2- concentration.
[0065] The dried ZrFe-BC was subjected to the above-mentioned adsorption reaction to investigate the adsorption capacity of the regenerated ZrFe-BC.
[0066] like Figure 4 As shown in the figure, with the increase of regeneration agent concentration, the removal rate is high when the desorption rate is high. With the increase of regeneration agent concentration, the desorption rate and secondary adsorption have a great influence on SO4 2- The removal rates of SO4 2- The removal rate reached a maximum value of 98.69%. When the concentration increased to 0.12 mol / L, the removal rate did not increase significantly. Therefore, the optimal regeneration agent concentration was selected as 0.10 mol / L.
[0067] like Figure 5 As shown, the regenerated ZrFe-BC adsorbs SO4 2- The capacity of ZrFe-BC without regeneration to SO4 2- The removal rate was 89.96%; after the first regeneration, SO4 2- The removal rate of ZrFe-BC was 85.3%, with a difference of only 5%, indicating that the first regeneration did not cause significant damage to ZrFe-BC, and also showed that ZrFe-BC has the potential for repeated regeneration. However, when the number of regenerations was 2, the reduction in removal rate was still small. When the number of regenerations was 4, ZrFe-BC had a significant reduction in removal rate of SO4 2- The removal rate dropped to 43.1%, but it still had a certain ability to be repeatedly regenerated.
[0068] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: the present application uses ginkgo leaves as raw materials to not only reduce SO4 2- , and also greatly reduces the cost of sewage treatment. The ginkgo leaves used are widely available and low in cost, which reduces the cost of sewage treatment. The zirconium iron salt modifier improves the adsorption capacity of ginkgo leaf biochar for sulfate, reducing the risk of sulfate in mine water. The production process of this application is simple.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a biochar adsorbent, characterized in that: The preparation method comprises: The ginkgo leaves are subjected to heating degradation and ball milling treatment in sequence to obtain crude biochar; A transition metal salt solution is added to the crude biochar to perform modification treatment to obtain the biochar adsorbent.
2. The preparation method according to claim 1, characterized in that: The ginkgo leaves are acidified ginkgo leaves; Preferably, the temperature of the heating degradation is 500-700°C; Preferably, the heating degradation time is 4-6 hours.
3. The preparation method according to claim 1, characterized in that: The grinding speed of the ball milling process is 300-350rpm; Preferably, the ball milling treatment time is 2-3 hours.
4. The preparation method according to claim 1, characterized in that: The transition metal salt solution comprises: ZrOCl2·8H2O and FeCl3; Preferably, the modification treatment comprises: adding the crude biochar and the transition metal salt solution into deionized water, and performing a first stirring in sequence to obtain a modified treatment solution; The pH value of the modified solution is adjusted, and the solution is stirred for the second time and allowed to stand, thereby completing the modification of the crude biochar.
5. The preparation method according to claim 4, characterized in that: In terms of mass ratio, the mass ratio of ZrOCl2·8H2O and FeCl3 is 7:3; Preferably, the pH value of the modified treatment liquid after the adjustment is 10-11.
6. The preparation method according to claim 1, characterized in that: After the modification, the preparation method further comprises: washing, centrifuging and drying the modified biochar in turn with water and ethanol.
7. A biochar adsorbent obtained by the preparation method according to any one of claims 1 to 6.
8. The biochar adsorbent obtained by the preparation method according to any one of claims 1 to 6 is used to adsorb SO4 in mine water 2- Application in.
9. A method for regenerating a biochar adsorbent obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The regeneration method comprises: The saturated biochar adsorbent is washed with deionized water, treated in a water bath in a NaOH solution and dried to obtain the regenerated biochar adsorbent.
10. The regeneration method according to claim 9, characterized in that: The water bath treatment comprises: immersing the adsorption saturated biochar adsorbent in the NaOH solution and stirring, and then washing to neutrality; Preferably, the concentration of the NaOH solution is 0.1-0.15 mol / L; Preferably, the temperature of the water bath treatment is 25-26°C; Preferably, the immersion time is 12-14 hours; Preferably, the biochar adsorbent can be regenerated no more than 4 times.
